PERFORMANCE OF ROOFTOP PHOTOVOLTAIC SYSTEM WITH ADDITIONAL WATER COOLING SYSTEM - Subur Priyono; Wahyu Wilopo; Mohammad Kholid Ridwan (Master in Systems Engineering, 2020)
Improving solar power plant performance is considered quite important for existing and prospective users of rooftop solar power plants in Indonesia due to its unattractive economic value. One of the efforts to optimize the performance is the application of an additional cooling system on the plant's photovoltaic module. This study aimed to determine the effectiveness of temperature reduction of the applied cooling system on solar panel productivity. The research was performed on the existing rooftop solar power plant with a capacity of 3 kWp, located in Depok City with coordinates of 6°38'03.40